Long-term Protection Against Herpes Zoster by the Adjuvanted Recombinant Zoster Vaccine: Interim Efficacy, Immunogenicity, and Safety Results up to 10 Years After Initial Vaccination - Strezova, Ana; Diez-Domingo, Javier; Al Shawafi, Kamal; Tinoco, Juan Carlos; Shi, Meng; Pirrotta, Paola; Mwakingwe-Omari, Agnes; Adams, Michael; Ahonen, Anitta; Andrews, Charles; Athan, Eugene; BarbaGómez, Jose-Fernando; et al. (Open forum infectious diseases, 2022)
Approximately 10 years after vaccination with the recombinant zoster vaccine (RZV), an interim analysis of this follow-up study of the ZOE-50/70 trials demonstrated that efficacy against herpes zoster remained high. Moreover, the safety profile remained clinically acceptable, suggesting that the clinical benefit of the RZV in ≥50-year-olds is sustained up to 10 years.